2012
DOI: 10.1017/s1368980012004442
|View full text |Cite
|
Sign up to set email alerts
|

Nut consumption and incidence of metabolic syndrome after 6-year follow-up: the SUN (Seguimiento Universidad de Navarra, University of Navarra Follow-up) cohort

Abstract: Objective: To assess the long-term relationship between tree nut consumption and the risk of developing metabolic syndrome (MetS). Design: Nut consumption was collected using a validated 136-item FFQ. The MetS was defined according to the International Diabetes Federation and American Heart Association/National Heart, Lung, and Blood Institute harmonizing definition. The association between nut consumption and MetS was assessed with logistic regression models adjusting for potential confounders. We compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…Similarly, it was found in a Mediterranean cohort study that participants who ate nuts two or more times per week had a significantly lower risk of weight gain (32). Moreover, nuts consumption is significantly associated with lower risk of developing metabolic syndrome (33). These results support the recommendation of nuts consumption without fear of weight gain.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, it was found in a Mediterranean cohort study that participants who ate nuts two or more times per week had a significantly lower risk of weight gain (32). Moreover, nuts consumption is significantly associated with lower risk of developing metabolic syndrome (33). These results support the recommendation of nuts consumption without fear of weight gain.…”
Section: Discussionsupporting
confidence: 62%
“…Insulin resistance, a key pathogenic link underlying the cluster of metabolic abnormalities seen in metabolic syndrome, is adversely effected by saturated fat and improved with MUFA [39-41]. Tree nuts, which are similar to avocado in dry weight composition including dietary fiber and MUFA content, have not been shown to increase body weight or metabolic syndrome risk in numerous clinical and epidemiological studies [42-46]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite their high energy and high fat content, nut consumption does not appear to induce weight gain in many intervention studies (29) and may increase satiation (30). Cross-sectional and prospective cohort studies showed that nut consumption was related to a low risk of metabolic syndrome (31, 32). Several short-term intervention studies suggested beneficial effects of nut consumption on lipid profile (33, 34), inflammatory markers and endothelial function (35), oxidative stress (36, 37), insulin secretion (38), and glucose homeostasis (39), which may explain the inverse association between habitual nut consumption and risk of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%